PENGARUH METODE MUFRADAT BERBASIS SMART CASSETE DALAM MENINGKATKAN KECAKAPAN BERBAHASA ARAB - Elzania Agustin; Herwina Bahar; Sundi, Venni Herli; Iswan; Bambang Eko Siagiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Smart Cassette-based mufradat method in improving Arabic language skills in grade I students of SD Islam Plus Al Muhajirin, Pondok Pucung - Jombang. The mufradat method is a learning technique that focuses on vocabulary mastery as a basis for language skills. Meanwhile, Smart Cassette is used as an interactive learning media that helps students understand, remember, and pronounce mufradat more effectively. This study uses an experimental method with a pre-test and post-test control group design. Based on the validity test table in this study, variable X (Mufradat Method) and variable Y (Arabic Language Skills) have been tested and obtained an r table of 0.444 and is said to be valid if r count> r table. The reliability test uses the Alpha Cronbach formula with a reliability value of 0.725. The N-Gain test shows that the average N-Gain Score for the control class is 0.111 with a low category, while the average N-Gain Score for the experimental class is 0.604 with a medium category. The normality test using the Shapiro Wilk formula was used to determine class normality, the level of significance of the ability to analyze in the control class and the experimental class was 0.05 from the significance criteria, then H0 was accepted and H1 was rejected. The homogeneity test that had been carried out had obtained a Levene statistic result of 0.350> 0.05 which meant that H0 was accepted and H1 was rejected. The T-Independent test obtained a t-test result of 3.683 with a significance value (2tailed) of 0.001 <0.05 which indicated that H0 was accepted and H1 was rejected. The results showed that there was a significant increase in the Arabic language skills of students using the Smart Cassette-based mufradat method compared to the control group. The conclusion of this study is that the Smart Cassette-based mufradat method can be an effective learning alternative in improving Arabic language skills in grade I students. This study is expected to contribute to the development of more innovative and interesting Arabic language learning methods for students at the elementary school level.